Emerging Christian Women at Uni: Intersection of Gender and Faith Identities on Campus - Morgans, Jenny (Research in the social scientific study of religion, 2022)
Gender and faith identities intersect in complex and fluid ways for ‘emerging’ Christian women in the intense time of transition at university. Based on qualitative research with 21 women students over a period of eighteen months, this research identifies the gendered and religious impact on emerging adulthood in two contexts: academic learning and ‘lad culture’, conversing with the work of Adrienne Rich in both contexts. This article introduces emerging adulthood and proposes that the ubiquitous postfeminist narrative among emerging women’s lives is a debilitating concern. Academic work is shown to be an area of exploration in which Christian students integrate their faith into their daily lives. However, it is often a space in which their gender is unwelcome and disregarded, negatively impacting their learning. On campus, lad culture is experienced by the women as a common injustice. However, engagement in Christian student activity often gives opportunity to either opt-out or to deny the prevalence of lad culture, including within Christian subcultures themselves. Finally, conclusions are offered in order to enable engagement and integration between student women’s faith, gender, and lived experiences at university.